Carpel size, grain filling, and morphology determine individual grain weight in wheat - Xie, Quan; Mayes, Sean; Sparkes, Debbie L. (Oxford University Press, 2015)
Individual grain weight is a major yield component in wheat. To provide a comprehensive understanding of grain weight determination, the carpel size at anthesis, grain dry matter accumulation, grain water uptake and loss, grain morphological expansion, and final grain weight at different positions within spikelets were investigated in a recombinant inbred line mapping population of bread wheat (Triticum aestivum L.)×spelt (Triticum spelta L.). Carpel size, grain dry matter and water accumulation, and grain dimensions interacted strongly with each other. Furthermore, larger carpels, a faster grain filling rate, earlier and longer grain filling, more grain water, faster grain water absorption and loss rates, and larger grain dimensions were associated with higher grain weight. Frequent quantitative trait locus (QTL) coincidences between these traits were observed, particularly those on chromosomes 2A, 3B, 4A, 5A, 5DL, and 7B, each of which harboured 16−49 QTLs associated with >12 traits. Analysis of the allelic effects of coincident QTLs confirmed their physiological relationships, indicating that the complex but orderly grain filling processes result mainly from pleiotropy or the tight linkages of functionally related genes. After grain filling, distal grains within spikelets were smaller than basal grains, primarily due to later grain filling and a slower initial grain filling rate, followed by synchronous maturation among different grains. Distal grain weight was improved by increased assimilate availability from anthesis. These findings provide deeper insight into grain weight determination in wheat, and the high level of QTL coincidences allows simultaneous improvement of multiple grain filling traits in breeding.